Design of a Dual Band Yagi Antenna For Amateur Radio At a VHF Frequency of 143 MHz - Cik Sadan; Zakuan Agung (ITEJ (Information Technology Engineering Journals), 2025)
Abstract—This research discusses the design and realization of a four-element Yagi antenna optimized for amateur radio communications in the VHF 143 MHz frequency band. The research process was carried out through simulations using CST Studio Suite software, antenna prototype assembly, and laboratory and field testing. The simulation results show that the antenna has a return loss of -22.14 dB, VSWR of 1.168, impedance of 50.23 Ω, and a gain of 7.613 dBi. After the antenna was realized, measurements using NanoVNA resulted in a return loss of -12 dB, VSWR of 1.4, impedance of 49.41 Ω, and a gain increasing to 10.9 dBi. Field testing proved that the antenna is able to work stably at a frequency of 143 MHz with an effective communication range of more than 10 km, although signal quality decreases at longer distances due to environmental obstacles and interference. Overall, the results of this study indicate that the designed four-element Yagi antenna meets the technical criteria of low VSWR, impedance approaching 50 Ω, adequate return loss, and high gain, making it suitable for use in supporting long-distance communications in amateur radio systems.